Pengembangan Sistem Rekomendasi Musik berdasarkan Waktu berbasis Android - Dwi Yovan Harjananto; Ratih Kartika Dewi; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In modern era, music has become an integral part towards many people, especially to accompany their daily activities. Further technological advancements such as the internet has affected and made easier the distribution of music for music affocionados. However for some, too many music in the distribution resulted in them having some difficulty in finding the one that suits their preference. Therefore, there exist a need for a system where music are grouped to small groups based on specific criteria-such as genre-and then recommending those to the user to ease their search. In realizing such system, the researcher conducts a research to develop a genre-based music categorization system. This recommendation system is developed as a mobile-based application in the Android operating system, where music that are recommended is based from surveys from scholars as well as using forward chaining algorythm. The system will recommend music within a databse in the form of playlist that is further segmented into the time of the day. Blackbox testing of the system is done with the intention to test the accuracy percentage of system's primary function. System Usability Scale test done to the system is also to measure the usability of said system, taken from testing the system to users directly.